TuxTeachings: the company as a learning space - Silva, Marlene; Costa, Daniela (Conferência - Investigação e Intervenção em Recursos Humanos, 2018)
The market has increasingly required professionals to develop their potential and their ongoing training. At the same time, companies have realized that their success is based on qualified human resources and talent retention, and therefore, it is essential to pay special attention to the development of each team member. This awareness of the importance of continuous development has helped companies to make a commitment to enrich their workforce by investing in training, naturally adapted to the specifics of the functions performed and the area of activity of the company. If training was once seen by companies as a cost, with return, today, this investment is made to be better prepared, as well as their teams, for any challenge that may arise. The organizations that allow the development of workers' skills and that allow them to learn continuously will be those with greater creative capacity, with better ideas and daily reinvention to achieve their goals. Basically, organizations need people who are smart, agile, and evolutionary. Aware of this premise, Eurotux presents itself as a qualifying company, allowing and impelling the transfer of knowledge and enhancing the learning of knowledge not associated with academic training. In this sense, in addition to the annual training plan that the company provides to its employees, which covers several areas of competence, Eurotux also presents the concept of TuxTeachings. TuxTeachings are internal training sessions on the most important technologies for each employee's role. The innovation here arises from the fact that they are carried out on the initiative of employees who have the possibility of participating, suggesting or leading internal training, with the support of the organization. In this way, Eurotux is not only a training space, but also becomes an object of training, fostering learning of the productive process and individual and collective knowledge, as well as sharing of values and socialization. This innovation in training allows a greater approximation between employees and their professional reality, updating their knowledge, validating them and allowing an increase of their self-esteem and their self-image. As such, both the employees and the company achieve a significant increase in productivity and profitability.